The Role of Perlindungan Anak Terpadu Berbasis Masyarakat (PATBM) Groups in Preventing and Handling Child Labour in the Informal Sector - Wahda, Muhammad Aksha; Sudirman, Sudirman (International Journal of Education, Information Technology, and Others, 2023)
This article describes the role of the Community-Based Integrated Child Protection (PATBM) group in preventing and handling child labour in the informal sector. This research is a qualitative method with data collection through in-depth interviews, non-participant observation, and literature review related to the object of research. This article will explain about (a) the concept of child labour and the problems faced, (b) how the prevention and handling mechanisms carried out by PATBM. This article explains that the lack of supervision in the informal sector causes children to be involved in various jobs that interfere with the fulfillment of children's rights and threaten their safety. By using the CLMRS system, the PATBM group in conducting supervision has succeeded in identifying various cases of child labour in the informal sector and remediating child labour.